PrEP as a Lifestyle and Investment for Adolescent Girls and Young Women in Sub-Saharan Africa. (18th February 2019) - Haberer, Jessica E.; Mugo, Nelly; Baeten, Jared M.; Pyra, Maria; Bukusi, Elizabeth; Bekker, Linda-Gail
Adolescent girls and young women (AGYW) are highly affected by the HIV epidemic, yet standard approaches to pre-exposure prophylaxis (PrEP) delivery will not meet their needs. This commentary highlights key characteristics of AGYW related to PrEP use and delivery, including typical neurocognitive development, lack of experience with sustained medication use, and the social and connected nature of AGYW's lives. We then suggest ways for programs to embrace these characteristics, such as presenting PrEP as a lifestyle choice and not a biomedical tool, making access to PrEP simple and easy, and recognizing the many influences AGYW face in taking PrEP. We also suggest ways for programs to identify AGYW at the highest risk of HIV acquisition. Adolescent girls and young women have an important role to play in ending the HIV epidemic and they deserve considerable, tailored investment.